Growth performance and hematological changes in growing pigs treated with Cordyceps militaris spent mushroom substrate - Waewaree Boontiam; Chalong Wachirapakorn; Suchat Wattanachai (Veterinary World, 2020)
Aim: This study was aimed to compare the efficacy of dietary Cordyceps militaris spent mushroom substrate (CMS) on growth performance, immunity, metabolic profiles, and antioxidant capacity in growing pigs.